First Experiences with Simultaneous Skeletal and Soft Tissue Reconstruction of Noma-Related Facial Defects - Giessler, Goetz A.; Borsche, André; Lim, Paul K.; Schmidt, Andreas B.; Cornelius, C.-Peter (Journal of Reconstructive Microsurgery, 2012)
Noma victims suffer from a three-dimensional facial soft-tissue loss. Some may also develop complex viscerocranial defects, due to acute osteitis, chronic exposure, or arrested skeletal growth. Reconstruction has mainly focused on soft tissue so far, whereas skeletal restoration was mostly avoided. After successful microvascular soft tissue free flap reconstruction, we now included skeletal restoration and mandibular ankylosis release into the initial step of complex noma surgery. One free rib graft and parascapular flap, one microvascular osteomyocutaneous flap from the subscapular system, and two sequential chimeric free flaps including vascularized bone were used as the initial steps for facial reconstruction. Ankylosis release could spare the temporomandibular joint. Complex noma reconstruction should include skeletal restoration. Avascular bone is acceptable in cases with complete vascularized graft coverage. Microsurgical chimeric flaps are preferable as they can reduce the number and complexity of secondary operations and provide viable, infection-resistant bone supporting facial growth.
Keywords: noma; chimeric flap; free fibula; medial femoral condyle corticoperiosteal flap; microvascular composite facial reconstruction